Effect of Combination of X-Ray Tube Current and Exposure Time on Contrast to Noise Ratio (CNR) using Computed Radiography - Utami, Ni Wayan Mega Savira; Ni Nyoman, Ratini; I Putu Eka, Juliantara (BULETIN FISIKA; Vol 23 No 1 (2022): BULETIN FISIKA February Edition, 2021)
A research has been carried out to determine the effect of the combination of X-ray tube current and exposure time on the Contrast to Noise Ratio (CNR) using Computed Radiography (CR). This study aims to determine the combination of X-ray tube current and exposure time on the quality of X-ray images using CR and the optimal value of its CNR. The tool used is a step wedge with an additional 1.5 mm thickness at each step, a constant tube voltage of 56 kV, an X-ray tube current and an exposure time of 5 mAs. Variations in the value of 5 mAs into the X-ray tube current and exposure time are as follows, variation 1 of 100 mA and 0.050 s, variation 2 of 125 mA and 0.040 s, variation 3 of 160 mA and 0.032 s, variation 4 of 200 mA and 0.025 s, and variation 5 of 250 mA and 0.020 s. Reading the values ??of I s , I b , and ? b using the RadiAnt DICOM VIEWER 2020.1 software program (64 bit) and analyzing the effect of the combination of X-ray tube current and exposure time on CNR values ??using IBM SPSS Statistic 26 with One Way-ANOVA Test. The results of the analysis showed that the combination of X-ray tube current and exposure time had no effect on the CNR value. The optimal value of CNR is 42.37, obtained in variation 3, namely the X-ray tube current is 160 mA and the exposure time is 0.032 s.